The Tamil Siddha medicine tradition - Bavani Arumugam (University of Malaya, 2024)
When a siddhar achieves Attama siddhis, they are referred to as intelligent and enlightened beings. Tamil literature, astronomy, astrology, medicine, alchemy, science, social philosophy, yoga, spirituality, physics, and many other disciplines have all benefited greatly from the contributions of the Siddhas. The practice of Siddha medicine precedes this contribution. Treatment of the three aspects of the human being—body, mind, and soul—is the focus of Siddha medicine. Tamil immigrants have brought siddha medicine, which is highly popular in South India, to other nations. On the palm leaves, the Siddhas jotted down the cures. Following independence, Siddha medicine was methodically compiled into a curriculum and is now offered as a required course in both public and private universities. Among the numerous fields the Siddhas left behind, Siddha medicine plays a major role in human health